Investigation of the efficiency and potential possibilities of paper protection by siloxan in wet environments - Osaulenko, Kseniia; Demchenko Valentynа; Merezhko, Nina (Technology audit and production reserves, 2017)
The object of research is unbleached pulp-based winding with a thickness of 70±3 μm. One of the main problems is the use of the research object as a packaging material. Particular attention is required to protect paper when it is used in wet conditions. The presence of a layer of adsorbed water on the surface can adversely affect the physical and technical properties. The degree of such influence is determined by the energy state of the surface of the substrate and by the wettability of its water in the liquid-crystal state and the adsorption of water vapor. To ensure the stability of this paper in aggressive media, its modifications are carried out by immersion in 3–5 %, by volume of the solution in water, organic solvents or an aqueous dispersion of organosilicon products. A study of the hydrophobic properties and the mushroom resistance of the surface of the treated paper is also carried out. The results of the investigation of the tensile strength and dielectric parameters of the treated paper are considered. For comparison, IR spectrometry of porous aluminosilicate glass is carried out. One of the main criteria is the tensile strength of the investigated paper treated with silicone coatings. As a result of the conducted studies, it is found that a less tensile force at the level of 84.6–90.1 % of the initial one is fixed when using coatings based on potassium methyl siliconate and its derivatives in various combinations. Therefore, in comparison with untreated paper, the modified one acquires high performance properties in terms of protection in humid environments.